1977
DOI: 10.1111/j.1651-2227.1977.tb07826.x
|View full text |Cite
|
Sign up to set email alerts
|

LONG‐TERM EFFECT ON MOTHER‐INFANT BEHAVIOUR OF EXTRA CONTACT DURING THE FIRST HOUR POST PARTUM II. A Follow‐up at Three months

Abstract: Primiparous mothers and their infants who had an extra 15-20 minutes' suckling and skin to skin contact during the first hour after delivery, behaved differently at 36 hours post partum compared with a control group without this extra contact. The present study is a 3-month follow-up of these mothers and infants by means of direct observation of mother-infant free play and a personal interview with the mothers. Mothers in the extra contact group spent more time kissing and looking en face at their infants; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(63 citation statements)
references
References 7 publications
4
56
2
1
Order By: Relevance
“…Hales and his co-researchers (Hales et al, 1977) reported that mothers given skin-to-skin contact with their infants immediately after delivery displayed significantly more affectionate behaviours at 36 hours than did control mothers. These findings were not confirmed by De Chateau and Wiberg (1977). Twenty-two primiparous mothers given extra skin-to-skin and suckling contact with their infants after delivery differed at 36 hours from a control group of primiparous and multiparous mothers receiving routine care, on only four out of 35 measured variables.…”
Section: Maternal Attachment In the Human Speciescontrasting
confidence: 74%
“…Hales and his co-researchers (Hales et al, 1977) reported that mothers given skin-to-skin contact with their infants immediately after delivery displayed significantly more affectionate behaviours at 36 hours than did control mothers. These findings were not confirmed by De Chateau and Wiberg (1977). Twenty-two primiparous mothers given extra skin-to-skin and suckling contact with their infants after delivery differed at 36 hours from a control group of primiparous and multiparous mothers receiving routine care, on only four out of 35 measured variables.…”
Section: Maternal Attachment In the Human Speciescontrasting
confidence: 74%
“…For instance, De Chateau and Wiberg (1977) reported that when mothers spent more time kissing their infants at suckling, the infants smiled more and cried less frequently. Affection exchange theory (AET: Floyd, 2002Floyd, , 2006a provides that communicating affection in close relationships initiates neuroendocrine processes that maximize reward and buffer the individual against the physiological effects of stress, and that these benefits are independent of those associated with receiving affectionate expressions.…”
Section: Kissing As a Stress-alleviating Behaviormentioning
confidence: 97%
“…In contrast, I have reported that relaxation by laughter or listening to Mozart reduces allergic responses and decreases allergen-specific IgE production [3][4][5]. It has been reported that mothers' kissing causes relaxation in healthy infants [6]. Moreover, I have previously reported that kissing by lovers or spouses to atopic patients reduces allergic responses and skews cytokine pattern toward Th1 type [7].…”
Section: Introductionmentioning
confidence: 89%